Cancer Detection Yield of TRUS-Guided Biopsy in Nepalese Men in the Fusion Biopsy Era - Khadga, Ajit; Adhikari, Mahesh Bahadur; Maharjan, Bipin; Gautam, Ravi Kiran; Mishra, Prashant; Basnet, Birodh; Yadav, Deepak Kumar; Pande, Kricha (Journal of Health Science and Medical Research, 2025)
Objective: Transrectal ultrasound (TRUS)-guided biopsy of the prostate is performed to obtain a histopathological diagnosis of prostate cancer and has been the mainstay of urological practice for years. In the era of fusion biopsy this study aimed to investigates the relevance of TRUS-guided biopsy and its role in cancer detection rates, particularly in resource-limited settings. Material and Methods: This retrospective study was carried out in a tertiary care institute. All symptomatic patients who underwent TRUS-guided biopsy for indication of raised serum prostate-specific antigen (PSA) level (>4 ng/mL) or suspicious digital rectal examination (DRE) findings (nodule, irregularity, hard consistency) from January 2021 to December 2023 were included. The data obtained were entered in statistics package for social sciences (SPSS). Statistical analyses used were Chi-square test and Spearman’s rank correlation analysis. Results: Out of the 77 patients included in the study, 24 were diagnosed with malignancy, resulting in an overall cancer detection rate of 31.16%. The detection rates for PSA levels of 4-10 ng/mL and 10-20 ng/mL were low, at 14.81% and 18.18%, respectively, while the rate exceeded 50% for PSA levels greater than 30 ng/mL. Additionally, 13 patients (16.88%) had post-biopsy complications, with one requiring hospital admission for fever. Conclusion: Despite advancements in fusion biopsy, TRUS-guided biopsy remains an essential diagnostic tool for prostate cancer. This study emphasizes the technique's ongoing significance, especially where access to advanced imaging modalities is limited, underscoring its crucial role in clinical decision-making.